The impacts of early marriages on societal development in Zimbabwe : the case of Manicaland from 2010- 2016. - Madhuku, Lorrein (Midlands State University, 2020)
In a way to enhance the eradication of early marriages in Zimbabwe the research was conducted on the impacts of early marriages on societal development. The research was conducted in Manicaland Province. The research objectives was to explain the causes of early marriages, impacts of early marriages, challenges faced in trying to eradicate early marriages as well as the effectiveness of legislative frameworks put in place to solve the problem of early marriages in Zimbabwe. It goes on to look on the strategies that can be implemented to eradicate early marriages. The study used mixed methods to collect data that is in-depth interviews and questionnaires. Data was also analysed using content and thematic analysis as it was presented in themes, graphs and tables. The research was being guided by liberal feminist theory and gender and power theory as they explain how women are being exploited in the society, viewed as of no value, hence becoming a driver of early marriages. In a research, it has been revealed that poverty is the major cause of early marriages leading to school dropouts, hence young potentials are not being given opportunity to show their capacity to the development of the society. Lack of funds has been said to be the major challenge faced as well as the lack of sound policies and poor implementation of them as the research revealed that those frameworks which were put in place in trying to stop early marriages are not effective as they are failing to implement them. The research then recommended that there should be inclusion of early marriages funds in the state budget, empowerment of girls, strict measures on those who practise early marriages as well as awareness campaigns in order to stop early marriages.